Methods of preparing a junior students law faculty for scientific researching work - Пильгун, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article is determining methods of involvement a junior students to the legal directionin researching. The main tasks is to clarity1 the elements of a systematic approach in preparing them for sciencework, development of creative thinking, forming a scientific worldview. mastering the methodology ofscientific knowledge.